Keunggulan Tongkat Dan Teguran Sebagai Pola Asuhan Mendidik Anak Dalam Hikmat Berdasarkan Amsal 29:15 - Vikson Huwae (Hymnos: Jurnal Teologi dan Keagamaan Kristen, 2024)
Proverbs 29:15 provides a method of parenting that is contrary to many laws today, especially the Child Protection Act No.39 of 1999, because it uses the rod. The use of a cane can be considered as an act of child abuse. Many previous studies have discussed the use of rattan as a method of educating children, but this study found that the combination of stick and reprimand is an excellent parenting method in educating children. Based on the hermeneutic research method of the sub-genre of wisdom literature, this research found two advantages of the parenting method offered by Proverbs 29:15: first, it is a balanced upbringing pattern; second, it has implications for the mental balance of children in their growth and development. This research will enrich the references and methods in parenting for educators and parents, as well as being an input for the development of wisdom literature research.